Clinical practice: Swallowing problems in cerebral palsy - Erasmus, Corrie E. (Springer-Verlag, 2011)
Cerebral palsy (CP) is the most common physical disability in early childhood. The worldwide prevalence of CP is approximately 2–2.5 per 1,000 live births. It has been clinically defined as a group of motor, cognitive, and perceptive impairments secondary to a non-progressive defect or lesion of the developing brain. Children with CP can have swallowing problems with severe drooling as one of the consequences. Malnutrition and recurrent aspiration pneumonia can increase the risk of morbidity and mortality. Early attention should be given to dysphagia and excessive drooling and their substantial contribution to the burden of a child with CP and his/her family. This review displays the important functional and anatomical issues related to swallowing problems in children with CP based on relevant literature and expert opinion. Furthermore, based on our experience, we describe a plan for approach of investigation and treatment of swallowing problems in cerebral palsy.